Changing Indications and Surgical Techniques for Corneal Transplantation Between 2004 and 2009 at a Tertiary Referral Center - Zare, Mohammad (Medknow Publications & Media Pvt Ltd, 2012)
PURPOSE: The aim of this study is to report the indications, techniques, and clinical outcomes of corneal transplantation and investigate any changing trends in surgical techniques over a 6 year period. MATERIALS AND METHODS: Records of patients who had undergone any kind of corneal transplantation at Labbafinejad Medical Center, Tehran, Iran, from January 2004 to December 2009 were reviewed to determine the indications and types of corneal transplantation. Postoperative best-corrected visual acuity, refractive error, graft clarity, and complications were reported. RESULTS: During this period, 1859 eyes of 1624 patients with a mean age of 41.3 ± 21.3 years underwent corneal transplantation. The most common indication was keratoconus (38.4%) followed by aphakic/pseudophakic bullous keratopathy (11.7%), previous failed grafts (10.6%), infectious corneal ulcers (10.1%), non-herpetic corneal scars (7.6%), trachoma keratopathy (4.7%), stromal corneal dystrophies (4.6%), post-herpetic corneal scar (3.7%), Fuchs’ endothelial dystrophy (0.8%), and congenital hereditary endothelial dystrophy (0.4%). Techniques of corneal transplantation included penetrating keratoplasty (PKP; 70.9%), deep anterior lamellar keratoplasty (DALK; 20.1%), conventional lamellar keratoplasty (LKP; 4.4%), and Descemet's stripping automated endothelial keratoplasty (DSAEK; 2.3%). Over the study period, there was a significant increase in the relative frequency of infectious corneal ulcers, failed grafts, and trachoma keratopathy. Additionally, a significant reduction was observed in PKP and LKP procedures, and volume of DALK and DSAEK increased significantly. At final follow-up, 69.0% of grafts were clear in the PKP group. This figure was 82.6%, 82.7%, and 97.6% in the DALK, LKP, and DSAEK groups, respectively. CONCLUSION: Keratoconus was the most common indication and PKP was the most prevalent technique used for corneal transplantation. However, significant changes in the indications and surgical techniques were observed from 2004 to 2009.